Frank and fearless: Supporting academic career progression for women in an Australian program - Polly Parker; Belinda Hewitt; Jennifer Witheriff; Amy Cooper (Administrative Sciences, 2018)
The underrepresentation of women in senior positions continues to be a major challenge in higher education and most other industries. In Australia, the career trajectory for academic women stalls at a lower level than that of their male counterparts. Concern about this situation in one Australian university led to the design and delivery of a career progression program to support women's advancement from senior lecturer to associate professor. This study details the main features of the program, designed to facilitate women's transition from being leading academics to academic leaders through a focus on leadership and career progression. We report the participants' perceptions of its value based on survey data. We conclude that leadership development is difficult work and requires a supportive environment where risk-taking is encouraged, where frank and fearless feedback is provided, and where the individual is required to examine assumptions and biases and to assume a leadership identity.
Keywords: 350; academic careers; gender; higher education; career progression; leadership